Variation of Ba concentration in some plants grown in industrial zone in Türkiye - Ayşe Öztürk Pulatoğlu (Informa UK Limited, 2023)
AbstractThis study was carried out on Fagus orientalis Lipsky (Oriental beech), Carpinus orientalis (Oriental hornbeam), and Quercus petraea (Matt.) Liebl. (Sessile oak) species that naturally spread out in the Çaycuma district of Zonguldak province, an industrial area in the northwestern Türkiye. The study aimed to determine the annual changes in barium (Ba) concentrations in the annual rings of the wood of the species. Moreover, Ba concentrations in the inner and outer bark were compared with the concentration in the wood, and changes in Ba concentration were determined by years and directions. As a result, the lowest mean Ba concentrations were found in hornbeam for all organs, whereas the highest values in the inner bark (944134 ppb) and wood (46996 ppb) were found in beech. The highest values in the outer bark were found in oak with 927482 ppb. For the three species, the values obtained on the outer side of the outer bark were higher. The study showed that all three species are useful in monitoring the changes in concentrations and the pollution of Ba in the air and can be used for this purpose. However, the most suitable species that can be used to reduce Ba concentration is Fagus orientalis, which has the highest Ba storage ability in the wood part.
Keywords: biomonitoring; Air pollution; barium; Forestry; heavy metal; SD1-669.5; air quality; 15. Life on land